2019
DOI: 10.18632/oncotarget.27287
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mutational burden in lung cancer: a systematic literature review

Abstract: Purpose: To assess the association of tumor mutational burden (TMB) with clinical outcomes, other biomarkers and patient/disease characteristics in patients receiving therapy for lung cancer. Results: In total, 4,303 publications were identified; 81 publications were included. The majority of publications assessing clinical efficacy of immunotherapy reported an association with high TMB, particularly when assessing progression-free survival and objective response rate. High TMB was consistently associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 110 publications
9
70
1
Order By: Relevance
“…When we set the cut-off at the upper 20 percentile (10.6 mt/mb), although patients with TMB-high still showed higher ORR (38.5 vs. 16%) and prolonged PFS (2.6 vs. 2.3 months) after ICB therapy, the differences were not significant. For TMB, recent systematic literature review of 81 prior publications concluded that standardized threshold for classifying TMB levels as low-and high-does not exist currently (29). In a large-scale study (n = 1,662) analyzing the association between TMB and clinical responses to checkpoint inhibitors in various cancer types (14), they used a top-20th percentile as a cutoff for TMB and suggested that that there may not be one universal definition of high TMB.…”
Section: Discussionmentioning
confidence: 99%
“…When we set the cut-off at the upper 20 percentile (10.6 mt/mb), although patients with TMB-high still showed higher ORR (38.5 vs. 16%) and prolonged PFS (2.6 vs. 2.3 months) after ICB therapy, the differences were not significant. For TMB, recent systematic literature review of 81 prior publications concluded that standardized threshold for classifying TMB levels as low-and high-does not exist currently (29). In a large-scale study (n = 1,662) analyzing the association between TMB and clinical responses to checkpoint inhibitors in various cancer types (14), they used a top-20th percentile as a cutoff for TMB and suggested that that there may not be one universal definition of high TMB.…”
Section: Discussionmentioning
confidence: 99%
“…10 For TMB, to our knowledge to date, the majority of studies have reported an association between high TMB and progression-free survival and the objective response rate when treated with immune checkpoint inhibitor therapy. 11 In addition, broader NGS-type panel testing can provide valuable information regarding the tumor's comutational profile, which may help to direct therapeutic choices in the future, such as the identification of inactivating STK11/LKB1 mutations in KRASmutated lung adenocarcinomas, which are predictive of primary resistance to immune checkpoint inhibitor therapy via PD-1 and/or PD-L1 blockade. 12 Therefore, as can be appreciated, the testing landscape for patients with advanced NSCLC in the United States has dramatically evolved over the past decade, expanding the number of biomarker-defined patient subgroups that are being matched with specific targeted therapies, thereby achieving superior clinical outcomes compared with previously relied on traditional cytotoxic chemotherapy.…”
Section: Current Recommendations For Nsclc Biomarker Testing In the Umentioning
confidence: 99%
“…TMB status can be assessed on tissue using whole-exome sequencing (WES) or targeted NGS of a more focused panel of genes [99,100]. Despite inconsistencies in the cut-offs definitions, high TMB appeared to be associated with greater clinical benefit (particularly ORR and PFS) among patients receiving immunotherapy for lung cancer [101]. However, the implementation of TMB assay into the clinic is hampered by several issues, including the tissue availability, which is limited to 34-59% of patients according to clinical trials [102][103][104].…”
Section: Baseline Identification Of Responder Patientsmentioning
confidence: 99%